Effect of preloading on haemodynamic of the patient undergoing surgery under spinal anaesthesia - Singh, J; Ranjit, S; Shrestha, S; Sharma, R; Marahatta, SB (Kathmandu University Medical Journal, 2010)
Background: Hypotension and bradycardia after conduction of spinal anaesthesia are common side effects because of sympathetic blockade. Efforts to prevent these complications have been attempted like preloading with crystalloids, colloids or use of vasopressors. The role of volume preloading to prevent haemodynamic changes associated with spinal anaesthesia has been recently questioned. Objective: The objective of the study was to investigate the effects of volume preload on changes of patient's hemodynamic. Materials and methods: A Quasi- experimental design was used to conduct the study. Taking written informed consent, 40 patients of age group 18-45 years and ASA grade I and II undergoing surgery under spinal anaesthesia in operation theatre of Dhulikhel Hospital were selected as the sample of the study and allocated randomly to 2 groups. Group I did not receive volume preload and Group II received preload of 1000 ml of Ringer's lactate solution within 30 minutes immediately before giving the spinal anaesthesia. An observational checklist was used to collect demographic, intraoperative and post-operative records of systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and heart rate (HR). Results: The findings revealed that the haemodynamic changes occurred in all patients. The decrease in SBP, MBP and DBP from baseline was statistically significant at all points of time (p=0.000). The decrease in HR from baseline was not statistically significant at all points of time (p>0.05). The overall incidence of hypotension was 50%, among which 9 (45%) were from without preload group and 11 (55%) were from with preload group. The incidence of hypotension was similar in groups, sexes and surgical conditions (General Surgery, Gynae/Obs and Orthopaedics). There were no significant differences in haemodynamic changes among groups. Conclusion: On the basis of findings, it is concluded that volume preloading had no effect on the incidence of hypotension and bradycardia after spinal anaesthesia. Key words: Preload; Haemodynamics; Spinal Anaesthesia; Crystalloid DOI: 10.3126/kumj.v8i2.3562 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 216-221